The Brief Wondrous Life of Oscar Wao: No Way Out but into the Cane Fields - McCurdy, Carol (FOCUS: Papers in English Literary and Cultural Studies, 2023)
The essay will focus on one aspect of Diaz’s symbolic representation of the fuku: the sugar cane fields of the Dominican Republic. What better place to address the curse of the diaspora, which all comes from “the same doomed, oppressive history that brought Columbus’ ships to America five hundred years ago” (Patteson 3). Much of the Dominican Republic’s traumatic history can be traced to its exportation of sugar grown in the cane fields, and to the brutality that occurred in these fields. In order to address the curse, Yunior structures the de Leon story around the Dominican cane fields that are central to the fuku and part of the Caribbean imagination.